Increasing Repurchase Intention through Experiential Marketing, Service Quality, and Customer Satisfaction - Lena Ellitan; Samuel Alfonso Sugiyanto; Andriya Risdwiyanto (Jurnal Maksipreneur, 2022)
Consumers can make repeat purchases for the umpteenth time for the same products and services on a regular basis. At the same time, consumers also pay attention to current and future situations and conditions. This study aims to understand the application of experiential marketing factors and service quality that can affect customer satisfaction and consumer intentions to make repeat purchases. The focus of this study is to analyze these factors in the service of Korean restaurants in Surabaya. This research is a causal type of quantitative research that uses the Structural Equation Model (SEM) analysis technique. Respondents in this study amounted to 175 Korean restaurant customers in Surabaya who were designated as objects in this study. Determination of respondents is done by using a purposive sampling technique. This study found that experiential marketing positively affects customer repurchase intention directly. That is, efforts to increase experiential marketing can increase customer intention to repurchase. This study also proves that service quality does not significantly affect customer intention to repurchase. This finding shows that service quality has become a fundamental factor considered normal for every restaurant service. Other results prove that the marketing experience is able to influence customers to make repeat purchases if they are satisfied with the products or services they consume.